Energy Saving in Spirit Distillation - Van Niekerk, S. v B. (South African Journal of Enology and Viticulture, 2017)
A simplified continuous wine spirit distillation plant was designed with the aim of saving energy, constructed and subsequently tested under full operational conditions. Duplication of the purification processes encountered in 6-column still operation was eliminated and the number of separate distillation columns reduced from six to four. The excellent separation of the alcohol from the impurities, achieved in a spacious purification column through adequate dilution of alcohol with water, is one of the outstanding characteristics of the adapted design. In addition, facilities for continuous caustic soda treatment of the impurities drastically reduced the percentage of feints. During distillation a continuous production of high quality spirit, with the still operating at 99% efficiency, was achieved. Distillation of inferior quality wine had no adverse effect on the quality of the distillate. Losses were minimal and steam consumption was reduced from 6,9 kg/L Absolute Alcohol, to 4,9 kg/LAA produced. The percentage feints requiring redistillation was reduced from ca. 20% to 1,0%.